2018
DOI: 10.1002/jpln.201800001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mineral nutrient concentrations and C‐N metabolism in cabbage shoots and roots following macronutrient deficiency

Abstract: The responses of metabolic networks to mineral deficiency are poorly understood. Here, we conducted a detailed, broad‐scale analysis of macronutrient concentrations and metabolic changes in the shoots and roots of cabbage (Brassica rapa L. ssp. pekinensis) plants in response to N, P, K, Ca, and Mg deficiency in nutrient solution. To standardize individual macronutrient‐deficient treatments, the concentrations of the other nutrients were maintained via substitution with other ions. Individual nutrient deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
(46 reference statements)
1
5
0
2
Order By: Relevance
“…Under the N limited condition, the growth and biomass of shoots were reduced, and the growth of roots was enhanced in Arabidopsis , cabbage, and rice [12,13,14,15,24]. In this study, under –N condition, the fresh weight of radish sprouts was reduced as in previous studies.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Under the N limited condition, the growth and biomass of shoots were reduced, and the growth of roots was enhanced in Arabidopsis , cabbage, and rice [12,13,14,15,24]. In this study, under –N condition, the fresh weight of radish sprouts was reduced as in previous studies.…”
Section: Resultssupporting
confidence: 64%
“…In Arabidopsis plants grown under –N condition, the total protein, and chlorophyll content, and fresh weight were decreased, and the content of anthocyanins, primary root length, and lateral root number were increased [13,14]. In cabbage, the growth was inhibited under –N condition, and the levels of most amino acids and organic acids were decreased compared to that under normal conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…The primary metabolites were measured using a non-targeted metabolomics using a comprehensive approach to evaluate different metabolomes under a specific set of conditions ( Son et al, 2016 ). We have previously applied the method to investigate metabolic changes in various crops, including tomato plants, in response to varying environmental factors, such as light or mineral nutrient supply ( Jung et al, 2013 ; Sung et al, 2015 ; Kim et al, 2018 ; Sung et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study with Oryza sativa L. it was shown that the levels of some phenolic acids were increased in plants with ND, in particular, the levels of p ‐coumaric acid and ferulic acid . It has also been reported that in shoots and roots of cabbage ( Brassica rapa L.) under ND, alternative biochemical pathways are activated that lead to the production of secondary metabolites such as quinate, which is a precursor of the shikimato pathway . Some of these events are correlated with an increase of phenylalanine ammonia lyase (PAL) activity , a key enzyme in the biosynthesis of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%